Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/jcm8050721
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Individuals with Dry Eye Symptoms without Clinical Diagnosis: Analysis of a Web-Based Survey

Abstract: Currently, the available treatment for dry eye disease (DED) varies. The present study aimed to investigate the characteristics of undiagnosed DED and patient-based self-care management for DED based on a web-based survey performed for Tear’s Day in Japan; 1030 participants (301 women) responded; 155 participants (72 women) had a clinical diagnosis of DED. We defined undiagnosed DED (n = 116; 54 women) as those with DED symptoms, as evaluated by a frequently used questionnaire despite not having a clinical dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…This heterogeneity made direct comparison between studies more challenging, if not impossible. In addition, several studies did not report their cut-off values for 'prolonged VDT use', thus not providing any information on the threshold limit for harmful daily VDT use duration (Hikichi et al 1995;Shimmura et al 1999;Viso et al 2009;Iyer et al 2012;Portello et al 2012;Bhargava et al 2014;Moon et al 2014;Kawashima et al 2015;Chałas et al 2018;Yamanishi et al 2019). Several of the studies using questionnaires only investigated CVS or related ocular symptoms, not DED.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity made direct comparison between studies more challenging, if not impossible. In addition, several studies did not report their cut-off values for 'prolonged VDT use', thus not providing any information on the threshold limit for harmful daily VDT use duration (Hikichi et al 1995;Shimmura et al 1999;Viso et al 2009;Iyer et al 2012;Portello et al 2012;Bhargava et al 2014;Moon et al 2014;Kawashima et al 2015;Chałas et al 2018;Yamanishi et al 2019). Several of the studies using questionnaires only investigated CVS or related ocular symptoms, not DED.…”
Section: Discussionmentioning
confidence: 99%
“…A three-step procedure can be a simple method for reaching the diagnosis of dry eye in 10 min in a low-tech office: (i) collect the patient's history by means of validated questionnaires and triage questions; (ii) observe without aid devices (e.g., skin, blinking) and with slit lamp biomicroscopy for the evaluation of inflammatory and/or eyelid disease; and (iii) perform first-level tests (break-up time, Schirmer test, vital dye staining, aesthesiometry) (Figure 1). A correct diagnosis able to determine the major causative factor(s) behind DED and assess disease severity is crucial for two main reasons, among others: (i) it will represent the basis for the choice of an appropriate therapeutic strategy [21]; and (ii) individuals who receive a diagnosis of DED had a significantly better DED-related quality of life (QoL) compared with those who did not [22]. In fact, a recent paper demonstrated that DED patients belonging to the undiagnosed group had a significantly worse score of DED-related QoL compared with patients who received a definitive diagnosis.…”
Section: False Myth #1: "Dry Eye Is Just a Disorder Or A Dysfunction"mentioning
confidence: 99%
“…Patients with dry eye disease frequently seek over-the-counter artificial tear drops, gels, ointments, or lubricants as their first-line pharmacotherapy treatment 3 . This decision may involve other health care professionals, such as pharmacists, general practitioners, optometrists, and ophthalmologists, 4–6 or patients may self-manage their symptoms without a formal diagnosis 7 …”
mentioning
confidence: 99%